Clinical, Histological, and Scintigraphic Comparative Study of the Use of Mandibular Bone Marrow and Peripheral Blood in Bone Neoformation. (31st December 2021) - Pasquali, Paulo José; André Dall'Agnol, Rodrigo; Garcia Rezende, Lucas; Martinez, Elizabeth Ferreira
Abstract : Background and Purpose . To evaluate the capacity of mandibular bone marrow blood aspirate associated with biomaterials to stimulate bone tissue neoformation compared to the use of peripheral blood aspirate in patients with bone loss in the premaxillary region. Materials and Methods . The study included 16 patients with maxillary atresia. The region was grafted with xenograft blocks associated with the following treatments: G1, the patient's peripheral blood during surgery, and G2, dripping of mandibular bone marrow blood until the xenograft was completely wet. After 7 and 14 days, scintigraphic images of the regions of interest (ROI) were taken to quantify pixels, which indicate osteogenic activity. Additionally, trephined samples obtained at the time of implant placement were stained in H&E, and newly formed bone tissue was quantified. The data were tabulated and statistically analyzed at a significance level of 5%. Results . Scintigraphic data showed greater osteogenic activity with mandibular bone marrow blood (G2) at all times evaluated p < 0.05 . As for the histomorphometric analysis, a greater amount of bone tissue was observed in samples treated with mandibular bone marrow blood (G2) compared to peripheral blood (G1) p < 0.05 . Conclusions . The appositional bone reconstruction technique in the block associated with mandibular bone marrow blood increased bone neoformation and osteogenic activity compared to conventional graft treatment with peripheral blood.